Negotiation of Condom Use in Female Sexual Workers in Hotspots in Kupang City - Ola, Claudia; Ndun, Helga; Maku, Grace M. (Universitas Nusa Cendana, 2024)
HIV and AIDS prevention is focused on key populations, including Female Sexual Workers (FSW), considering the high risk of HIV transmission. Negotiation to offer condoms become a necessary skill for FSW to convince their clients in limiting the transmission. This study aims at exploring the condomn negotiation among FSW working in hotspots in Kupang City. The study was qualitative with phenomenological approach. Informants consisted of 10 FSWs selected by purposive sampling technique. Data were analyzed using thematically. Cues to negotiate condom use was found to be internally and externally. FSWs with confidence were able to start negotiation, and kept trying to persuade the clients, and stopped the transaction if clients refused the offer. Benefits of condoms and negotiation skill need to be improved among FSWs to help build their confidence and consistency in persuading clients to wear condoms.